PREOPERATIVE INTRAVENOUS TRAMADOL FOR PERCUTANEOUS NEPHROSTOMY TO REDUCE INTRAOPERATIVE PAIN - Oetama, Harris; Sihombing, Aaron Tigor (Indonesian Journal of Urology, 2019)
Objective: To evaluate the effect of additional preoperative intravenous tramadol for reducing intraoperative pain. Material & Methods: This study was a double blind randomized controlled study from April - June 2017 in Urology Department in Hasan Sadikin Hospital. Inclusion criteria were cervical cancer patients who were performed percutaneous nephrostomy. Exclusion criteria were patients with infection and pain before the procedure. Written informed consent was obtained from each patient and the study protocol was approved by the local human ethics committee. The subjects were randomly divided into 2 groups. Group A were given 100 ml dripped normal saline 1 hour before the procedure and intraoperative local anesthesia with lidocaine 2% and group B were given preoperative intravenous tramadol 100 mg dripped within 100 ml of normal saline 1 hour before the procedure and intraoperative lidocaine 2%. Visual Analogue Score (VAS) were used to evaluate the pain score. All calculation were done using SPSS version 20. Results: There were 60 cervical cancer patients who were performed percutaneous nephrostomy (29 patients in Group A and 31 patients in Group B). The mean age in group A was 48.86 ± 8.524 (years old) and the mean age in group B was 51.90 ± 6.76 (years old). The median VAS score in group A was 4, with the minimum score was 2.00, maximum score was 6.00. The median VAS score in group B was 2, with the minimum score was 0.00, maximum score was 4.00. In group A, 11 patients (18.3%) were mild pain, 16 patients (26.7%) were moderate pain, 2 patients (3.3%) were severe pain. In group B, 29 patients (48.3%) were mild pain, 2 patients (3.3%) were moderate pain, 0 patients (0.0%) were severe pain. Based on Mann-Whitney U test, there was a significant pain score reduction in group B compared to group A (p=0.0001). There were no significant differences in the prevalence or proportion of patients with nausea and vomiting in group A and B (10% and 12%, respectively). There were no other adverse events and other complications observed in both groups. Conclusion: Preoperative intravenous tramadol significantly reduced intraoperative pain in cervical patients who were performed percutaneous nephrostomy compare to those who were only given intraoperative local anesthesia.